1981
DOI: 10.1161/01.res.48.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Role of the intrarenal renin-angiotensin system in the control of renal function.

Abstract: IN THIS review article, we will assess the evidence for the presence and the mechanism of the intrarenal renin-angiotensin system acting as a local hormonal system in the control of renal function. First, we will review the evidence for the presence of a renin-angiotensin system in the kidney. Second, using results of our own and other studies, we will develop the concept that the intrarenal renin-angiotensin system acts as a local hormonal system in the control of renal function. Third, we will discuss experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(58 citation statements)
references
References 72 publications
3
55
0
Order By: Relevance
“…Since this would more than compensate for the hypotensive effect that resulted from removal of A II from plasma, blood pressure would rise above the control level. This explanation supports the concept of intrarenal production of A II as one component of an intrarenal renin-angiotensin system (Levens, Peach & Carey, 1981;Mendelsohn, 1982 (Peach, 1977 (Freeman, Davis & Lohmeier, 1975;Taub, Caldicott & Hollenberg, 1977;Caldicott, Taub, Margulies & Hollenberg, 1981). Other investigators however have reported that in the dog, A II is a more potent renal vasconstrictor than A III and demonstrated that this was not due to differential release of prostaglandins (Satoh, Itsukaichi, Ohyama & Hayashi, 1981).…”
Section: Discussionsupporting
confidence: 61%
“…Since this would more than compensate for the hypotensive effect that resulted from removal of A II from plasma, blood pressure would rise above the control level. This explanation supports the concept of intrarenal production of A II as one component of an intrarenal renin-angiotensin system (Levens, Peach & Carey, 1981;Mendelsohn, 1982 (Peach, 1977 (Freeman, Davis & Lohmeier, 1975;Taub, Caldicott & Hollenberg, 1977;Caldicott, Taub, Margulies & Hollenberg, 1981). Other investigators however have reported that in the dog, A II is a more potent renal vasconstrictor than A III and demonstrated that this was not due to differential release of prostaglandins (Satoh, Itsukaichi, Ohyama & Hayashi, 1981).…”
Section: Discussionsupporting
confidence: 61%
“…For example, increased renal prostaglandins preserve renal blood flow when cardiac output is low ( 16). There is increasing evidence that the kidney also contains a local RAS that may operate independently of the circulating RAS (17)(18)(19)(20)(21). The expressions of renin and angiotensinogen genes in the kidney have been demonstrated (20,22).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, we observed a continuous activation of the RAAS by long-term inhibition of ANP, and angiotensin II causes vasoconstriction of the efferent arteriole as well as an increase in sodium reabsorption in proximal tubules. 26,27 Since the renal functions changed in proportion to the RAAS, the activated RAAS may play a part in the decreases in urinary water and sodium excretion, GFR and RPF in this study.…”
Section: Changes In Renal Functionsmentioning
confidence: 73%